HTLS Conductors: A Way to Optimize RES Generation and to Improve the Competitiveness of the Electrical Market—A Case Study in Sicily. (6th September 2018) - Ippolito, M. G.; Massaro, F.; Cassaro, C.
Abstract : Stringent environmental constraints make more difficult to identify new energy corridors and build new power lines. The increase in the generation of electricity from renewable energy sources (RESs) makes the operation of electrical systems increasingly difficult in some areas. The transmission system operators (TSOs), in Italy Terna, are forced to exploit the existing overhead transmission lines, increasing the possibility of dispatching energy, in particular RES, optimizing the transmission capacity. Therefore, after a brief presentation of the Sicilian electricity system and a brief description of high-temperature low-sag (HTLS) conductors, a case study is presented. It is shown how it is possible to optimize the dispatching from renewable sources and, finally, it is demonstrated how the use of HTLS conductor can contribute, together with other actions taken by the TSO, to the decrease of the zonal price of electricity, to the creation of a market with fewer constraints and to new operating conditions that increase the resilience of the electricity system in case of disturbances.